Attracting and developing STEMM talent toward excellence and innovation - Stoeger, Heidrun; Luo, Linlin; Ziegler, Albert (Annals of the New York Academy of Sciences, 2024)
This article provides an overview of science, technology, engineering, mathematics, and medical sciences (STEMM) talent development from first exposure to a STEMM domain to achieving eminence and innovation. To this end, a resource-oriented model of STEMM talent development is proposed as a framework. It includes a three-stage phase model based on Bloom (1985), with the main focus on interest development in the first stage, skill acquisition toward expertise and excellence in the second stage, and style formation toward eminence and innovation in the final stage. A literature review shows that from an educational perspective, each phase is mainly characterized by the focus that Bloom postulated. However, it is important that all three stages (i.e., interest development, skill acquisition, and style formation) occur in a stage-typical manner. To explain how these primary objectives of STEMM development can be supported through STEMM talent education, Ziegler and Stoeger's (2011) educational and learning capital framework is used in the proposed resource-based model. A literature review shows that consistent provisioning of the resources specified in the model is necessary for individuals to complete a learning pathway to STEMM eminence and innovation.
CRIS-Team Scopus Importer:2024-03-22
Keywords: educational capital; innovation; learning capital; learning resources; STEMM; talent development